Nocardia prosthetic knee infection successfully treated by one-stage exchange: case report and review. Issue 4 (August 2015) - Laurent, F.; Rodriguez-Villalobos, H.; Cornu, O.; Vandercam, B.; Yombi, J. C.
<x content-type="archive" xml:space="preserve">Abstract</x> A 64-year-old man with a history of sarcoidosis on corticosteroids and azathioprine was admitted to our hospital with complaints of worsening left knee pain and swelling for the past 3 weeks. His past medical history is also significant for severe osteoarthritis requiring a cemented total left knee arthroplasty 1 year ago. Diagnostic investigation during his hospital admission eventually led to the diagnosis of Nocardia nova knee prosthetic joint infection in the setting of a disseminated nocardiosis. He was successful treated by one-stage complete hardware exchange in conjunction with an adapted antibiotic therapy regimen (meropenem and doxycycline followed by ceftriaxone and doxycycline). Two years later, his recovery was deemed excellent.